2009
DOI: 10.1073/pnas.0901202106
|View full text |Cite
|
Sign up to set email alerts
|

Newcomer insulin secretory granules as a highly calcium-sensitive pool

Abstract: Insulin secretion is biphasic in response to a step in glucose stimulation. Recent experiments suggest that 2 different mechanisms operate during the 2 phases, with transient first-phase secretion due to exocytosis of docked granules but the second sustained phase due largely to newcomer granules. Another line of research has shown that there exist 2 pools of releasable granules with different Ca 2؉ sensitivities. An immediately releasable pool (IRP) is located in the vicinity of Ca 2؉ channels, whereas a high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
121
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 93 publications
(128 citation statements)
references
References 61 publications
(117 reference statements)
7
121
0
Order By: Relevance
“…This model was used (Pedersen et al, 2010) to show how cell heterogeneity might underlie the fact that the pancreas senses not only the plasma glucose concentration, but also how rapid the glucose concentration increases (Breda et al, 2001(Breda et al, , 2002. Other models describe the dynamics of granules as they move between different pools, and the control of exocytosis by Ca 2+ (Bertuzzi et al, 2007;Chen et al, 2008;Pedersen and Sherman, 2009). Using such a model it was suggested (Pedersen and Sherman, 2009) that a highly Ca 2+ -sensitive pool, described by capacitance measurements (Wan et al, 2004;Yang and Gillis, 2004) could correspond to newcomer granules seen in TIRF microscopy experiments (Ohara-Imaizumi et al, 2004), illustrating how mathematical models can be used to integrate data obtained with different techniques and on different timescales.…”
Section: Mathematical Modeling Of Granule Dynamics In Rodent β-Cellsmentioning
confidence: 99%
See 2 more Smart Citations
“…This model was used (Pedersen et al, 2010) to show how cell heterogeneity might underlie the fact that the pancreas senses not only the plasma glucose concentration, but also how rapid the glucose concentration increases (Breda et al, 2001(Breda et al, , 2002. Other models describe the dynamics of granules as they move between different pools, and the control of exocytosis by Ca 2+ (Bertuzzi et al, 2007;Chen et al, 2008;Pedersen and Sherman, 2009). Using such a model it was suggested (Pedersen and Sherman, 2009) that a highly Ca 2+ -sensitive pool, described by capacitance measurements (Wan et al, 2004;Yang and Gillis, 2004) could correspond to newcomer granules seen in TIRF microscopy experiments (Ohara-Imaizumi et al, 2004), illustrating how mathematical models can be used to integrate data obtained with different techniques and on different timescales.…”
Section: Mathematical Modeling Of Granule Dynamics In Rodent β-Cellsmentioning
confidence: 99%
“…Other models describe the dynamics of granules as they move between different pools, and the control of exocytosis by Ca 2+ (Bertuzzi et al, 2007;Chen et al, 2008;Pedersen and Sherman, 2009). Using such a model it was suggested (Pedersen and Sherman, 2009) that a highly Ca 2+ -sensitive pool, described by capacitance measurements (Wan et al, 2004;Yang and Gillis, 2004) could correspond to newcomer granules seen in TIRF microscopy experiments (Ohara-Imaizumi et al, 2004), illustrating how mathematical models can be used to integrate data obtained with different techniques and on different timescales. This link between Ca 2+ -sensitivity and fusion mode was partly confirmed experimentally (Ohara-Imaizumi et al, 2009).…”
Section: Mathematical Modeling Of Granule Dynamics In Rodent β-Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, the model does not consider Ca 2þ dynamics, which is known to have complex temporal patterns with a first phase of raised cytosolic Ca 2þ concentrations followed by oscillations [22]. It is most likely that both granule pool dynamics and Ca 2þ patterns contribute to the typical biphasic secretion patterns seen after a rapid rise in glucose [23], such as following the glucose bolus in the IVGTT, as well as other secretion profiles. It will be interesting to investigate the relative contribution of Ca 2þ versus granule pool dynamics to IVGTT and OGTT insulin secretion profiles following the multiscale ideas presented in Pedersen et al [7] and in the present article.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to note that AMG9810 does not inhibit GSIS completely, even at high concentrations, which suggests that the TRPV1-R in -cells only partially contributes to the total Ca 2+ influx needed for exocytosis. It has been suggested that in islet -cells, while the 1 st phase insulin secretion is coupled to L-type Ca 2+ channels, the 2 nd phase secretion is probably coupled to R-type Ca 2+ channels (Jing et al, 2005;Pedersen and Sherman, 2009). …”
Section: Discussionmentioning
confidence: 99%